A case of bunashimeji mushroom‐induced hypersensitivity pneumonitis diagnosed by inhalational provocation test in a hospital room - Tomoe Akagami; Kazuyuki Nakagome; Sotaro Takagi; Susumu Yamazaki; Shohei Minezaki; Hidetoshi Nakamura; Kenji Tsushima; Makoto Nagata (Respirology Case Reports, 2023)
Abstract A 66‐year‐old woman was admitted to our hospital with a 2‐month history of dry cough and exertional dyspnea. She had worked as a mushroom farmer and had been exposed to mushroom for more than 40 years. The patient showed elevated levels of KL‐6 (2966 U/mL) and surfactant protein D (410 ng/mL), and computed tomography of the chest revealed ground‐glass opacities and fine nodular shadows in both lungs, suggesting mushroom‐induced hypersensitivity pneumonitis. Pulmonary function testing revealed decreases in forced vital capacity (78% of predicted) and carbon monoxide diffusing capacity (67% of predicted). The inhalational provocation test was positive for bunashimeji mushrooms. Precipitating antibody was only identified for spores or bodies of bunashimeji mushrooms, and lymphocyte stimulation testing with spores or bodies of bunashimeji mushrooms also yielded positive results. Bunashimeji mushroom‐induced hypersensitivity pneumonitis was therefore diagnosed. Radiological findings and pulmonary function were improved by corticosteroid therapy and the patient has since remained healthy with allergen avoidance.